Rapid regeneration method of waste plastic

By pretreating and preparing modified composite agents, recycled polyethylene fibers with flame retardant and antibacterial properties are prepared, which solves the problems of degradation of quality and flammability and pollution after recycling of waste plastics, and realizes high-value-added recycled plastic products production.

CN119241936APending Publication Date: 2025-01-03SHENZHEN MATERIAL & RECYCLING ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411435520.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-03

Smart Images

  • Figure CN119241936A_ABST
    Figure CN119241936A_ABST
Patent Text Reader

Abstract

The invention provides a rapid regeneration method of waste plastics, and belongs to the technical field of solid waste recovery. Comprising the following steps: pretreating waste plastic; stirring and mixing; regenerating polyethylene fibers; and preparing the regenerated cloth bag. According to the preparation method, the ammonium polyphosphate solution and the graphene oxide dispersion liquid are prepared respectively, and the ammonium polyphosphate solution and the graphene oxide dispersion liquid are mixed and subjected to ultrasonic treatment to prepare the composite coating material, so that the ammonium polyphosphate is loaded on the graphene oxide with a high specific area, and the stability and the flame retardant property of the ammonium polyphosphate are improved; finally, the composite coating material and 3-(3, 5-di-tert-butyl-4-hydroxyphenyl) propionate are subjected to a mixed reaction to prepare a composite flame retardant, and the 3-(3, 5-di-tert-butyl-4-hydroxyphenyl) propionate is used for conducting graft modification on the surface of the composite coating material, so that the compatibility between the composite flame retardant and the waste polyethylene plastic is improved, and the flame retardant property of the waste polyethylene plastic is improved. Further, the flame retardant property of the prepared regenerated cloth bag is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste recycling, and in particular to a method for rapid regeneration of waste plastics. Background Art

[0002] Waste plastics usually refer to plastic products and scraps that are discarded during use or generated during the production and processing process and no longer have use value. Such plastic materials have lost their original use and become solid waste. Waste plastics can be divided into many types according to their sources, such as PET (polyethylene terephthalate) bottles, HDPE (high-density polyethylene) containers, PVC (polyvinyl chloride) products, LDPE (low-density polyethylene) films, PP (polypropylene) products, etc. They may come from households, commercial activities, construction or industrial production processes. Waste plastics pose a huge challenge to the environment because they degrade extremely slowly in the natural environment, which may take decades to hundreds of years. Improperly handled waste plastics will pollute soil and water bodies and cause harm to wildlife and plants. Therefore, the recycling and proper disposal of waste plastics have become environmental issues of global concern, and various treatment methods including recycling, chemical recycling, and energy recovery have been widely discussed and practiced.

[0003] At present, although existing plastic recycling technologies have made certain progress, including physical recycling, chemical recycling and energy recovery, there are still many difficulties in converting waste plastics into high-value-added products. Especially for products such as plastic bottles that are discarded after a single use, because the commonly used materials such as PE (polyethylene) have high durability and a long natural degradation cycle, the quality of the recycled materials decreases, limiting the scope and value of their reuse. In addition, traditional plastic bags are flammable in fires, increasing fire hazards, and the lack of antibacterial properties will lead to the growth of bacteria and mold, affecting food hygiene and medical safety.

[0004] Therefore, it is necessary to propose a rapid regeneration method for waste plastics that can regenerate plastic products with flame retardant and antibacterial functions. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for rapid regeneration of waste plastics.

[0006] A method for rapid regeneration of waste plastics comprises the following steps:

[0007] S1: Pre-treatment of waste plastics

[0008] The waste polyethylene plastic is cleaned and disinfected, and then placed in a grinder for full crushing to obtain plastic scraps;

[0009] S2: Stirring and mixing

[0010] The plastic scraps are passed through a 100-200 mesh sieve, and then placed in a high-speed mixer together with the modified composite antibacterial agent and the composite flame retardant, and mixed and stirred at a rate of 800-1000 r / min for 1-2 hours to obtain a mixed material;

[0011] S3: Recycled polyethylene fiber

[0012] The mixed material, polyethylene resin and glass fiber are added into a screw injection molding machine, heated and melted for spinning, and stretched under the action of hot air to obtain recycled polyethylene fiber;

[0013] S4: Preparation of recycled cloth bags

[0014] The recycled polyethylene fibers are drawn by a drafting airflow, vertically directed to a drum, and collected on a flat plate, thermally bonded to form recycled cloth, and then the recycled cloth is processed into recycled cloth bags;

[0015] Calculated by mass percentage, the raw material components of the recycled polyethylene fiber include: 3-5% modified composite antibacterial agent, 3-5% composite flame retardant, 10-15% polyethylene resin and 15-20% glass fiber, and the remainder is plastic scraps.

[0016] Furthermore, the preparation steps of the composite flame retardant are as follows:

[0017] A1: Add ammonium polyphosphate to anhydrous ethanol at a solid-liquid ratio of 1g:(2.5-3.5)mL, stir and dissolve to obtain an ammonium polyphosphate solution, and add graphene oxide to deionized water at a solid-liquid ratio of 1g:(60-70)mL, stir and disperse to obtain a graphene oxide dispersion;

[0018] A:2: The above ammonium polyphosphate solution and graphene oxide dispersion are fully stirred and mixed, and then heated at 40-50°C and ultrasonically treated for 20-24h, and then centrifuged, washed and dried to obtain a composite coating material;

[0019] A3: Add 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to dimethylformamide at a solid-liquid ratio of 1g:(30-40)mL, stir thoroughly to dissolve, then add the above composite coating material, ultrasonically treat for 20-30min, fully disperse, and obtain a composite dispersion;

[0020] A4: Add epichlorohydrin to the above composite dispersion, heat and stir at 75-85°C for 3-4 hours, cool naturally to room temperature, filter, wash and dry to obtain a composite flame retardant.

[0021] Furthermore, the preparation steps of the modified composite antibacterial agent are as follows:

[0022] B1: Mix the composite antibacterial agent with deionized water and anhydrous ethanol at a solid-liquid ratio of 1 g: 1 mL: (20-30) mL, stir for 20-30 min, and ultrasonically disperse for 10-20 min to obtain a composite antibacterial agent dispersion;

[0023] B2: Add silane coupling agent to the above composite antibacterial agent dispersion, then add sodium hydroxide solution to adjust the pH to 5-6, then heat and stir under reflux at 70-80°C for 3-4h, filter, wash and dry to obtain a surface-modified composite antibacterial agent;

[0024] B3: Add the surface modified composite antibacterial agent into white oil at a mass ratio of 1:(46-50), stir and disperse thoroughly to obtain liquid A;

[0025] B4: Add acrylamide and acrylic acid to deionized water in a volume ratio of 1: (3-5): (90-96), stir and mix thoroughly, then add a crosslinking agent, continue stirring and mixing to obtain liquid B;

[0026] B5: Evenly mix equal masses of the above-mentioned liquid A and liquid B, ultrasonically emulsify for 20-30 minutes, add ammonium persulfate, heat and stir under argon protection at 60-70°C for reflux reaction for 4-5 hours, and then centrifuge, wash and dry to obtain a modified composite antibacterial agent.

[0027] Furthermore, the preparation steps of the composite antibacterial agent are as follows:

[0028] C1: Add zinc nitrate hexahydrate into methanol at a solid-liquid ratio of 1 g: (25-35) mL, stir thoroughly to dissolve, and obtain a zinc nitrate solution;

[0029] C2: Add 2-methylimidazole to methanol at a solid-liquid ratio of 1 g: (40-50) mL, stir thoroughly to dissolve, and obtain a 2-methylimidazole solution;

[0030] C3: adding the 2-methylimidazole solution to the zinc nitrate solution, ultrasonically treating for 10-20 minutes, mixing thoroughly, and then adding the bismuth nitrate solution while stirring to obtain a composite solution;

[0031] C4: The above composite solution is transferred to a high-pressure reactor, heated at 120-130°C for reaction for 20-24 hours, naturally cooled to room temperature, filtered, washed and dried, and then placed in a muffle furnace for heat treatment at 300-400°C for 2-3 hours to obtain a composite antibacterial agent.

[0032] Furthermore, the volume ratio of the ammonium polyphosphate solution to the graphene oxide dispersion is 1:(2-2.2).

[0033] Furthermore, the mass ratio of the composite coating material to 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 1:(2-4), and the amount of epichlorohydrin added is 4-6% of the mass percentage of the composite dispersion.

[0034] Furthermore, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the added amount of the silane coupling agent is 6-8% by mass of the composite antibacterial agent dispersion.

[0035] Furthermore, the crosslinking agent is N,N'-methylenebisacrylamide, and the added amount of the crosslinking agent is 0.1-0.3% of the mass percentage of acrylamide, and the added amounts of ammonium persulfate and the crosslinking agent are equal.

[0036] Furthermore, the volume ratio of the zinc nitrate solution to the 2-methylimidazole solution is 1:(1.2-1.8).

[0037] Furthermore, the volume ratio of the bismuth nitrate solution to the zinc nitrate solution is 1:(90-110), and the concentration of the bismuth nitrate solution is 1 mol / L.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. The present invention prepares an ammonium polyphosphate solution and a graphene oxide dispersion respectively, and mixes the ammonium polyphosphate solution and the graphene oxide dispersion to prepare a composite coating material by ultrasonic treatment, so that the ammonium polyphosphate is loaded on the graphene oxide with a high specific area to improve the stability and flame retardant properties of the ammonium polyphosphate. Finally, the composite coating material is mixed with 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to prepare a composite flame retardant, and the surface of the composite coating material is grafted and modified by 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to improve the compatibility between the composite flame retardant and waste polyethylene plastics, thereby improving the flame retardant properties of the obtained recycled cloth bag.

[0040] 2. The present invention prepares a composite antibacterial agent by first dissolving zinc nitrate hexahydrate and 2-methylimidazole in methanol respectively to prepare a zinc nitrate solution and a 2-methylimidazole solution, and then fully mixing the silver nitrate solution and the 2-methylimidazole solution, and adding a bismuth nitrate solution to heat and react, so that bismuth oxide with antibacterial activity is uniformly loaded on the porous zinc-based metal organic framework. Since metallic zinc also has certain antibacterial activity, after the zinc-based metal organic framework is loaded with bismuth oxide, not only the antibacterial durability of bismuth oxide can be improved, but the two can also synergistically fight bacteria, so that the prepared composite antibacterial agent has a better and longer-term antibacterial effect.

[0041] 3. The present invention uniformly disperses the composite antibacterial agent in a mixed solution of deionized water and anhydrous ethanol, then adds a silane coupling agent to react, and performs surface modification on the composite antibacterial agent. The surface modified composite antibacterial agent is then subjected to surface graft copolymerization reaction with acrylamide and acrylic acid under the conditions of a cross-linking agent and an ammonium persulfate initiator, thereby modifying the composite antibacterial agent to improve the compatibility between the composite antibacterial agent and waste polyethylene plastics, thereby achieving the effect of improving the antibacterial properties of the obtained recycled cloth bag. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.

[0043] Figure 1 This is a flow chart of the method for rapid regeneration of waste plastics adopted in an embodiment of the present invention. DETAILED DESCRIPTION

[0044] The following is a detailed description of a method for rapid regeneration of waste plastics provided by the present invention through specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternatives to implement some known technologies.

[0045] Example 1

[0046] A rapid recycling method for waste plastics, such as Figure 1 As shown, the following steps are included:

[0047] S1: Pre-treatment of waste plastics

[0048] The waste polyethylene plastic is cleaned and disinfected, and then placed in a grinder for full crushing to obtain plastic scraps;

[0049] S2: Stirring and mixing

[0050] The plastic scraps were passed through a 100-mesh sieve, and then placed in a high-speed mixer together with the modified composite antibacterial agent and the composite flame retardant, and mixed and stirred at a rate of 800 r / min for 1 hour to obtain a mixed material;

[0051] S3: Recycled polyethylene fiber

[0052] The mixed material, polyethylene resin and glass fiber are added into a screw injection molding machine, heated and melted for spinning, and stretched under the action of hot air to obtain recycled polyethylene fiber;

[0053] S4: Preparation of recycled cloth bags

[0054] The recycled polyethylene fibers are drawn by a drafting airflow, vertically directed to a drum, and collected on a flat plate, thermally bonded to form recycled cloth, and then the recycled cloth is processed into recycled cloth bags;

[0055] The raw material components of the recycled polyethylene fiber include, by mass percentage, 3% of a modified composite antimicrobial agent, 3% of a composite flame retardant, 10% of a polyethylene resin and 15% of glass fiber, with the remainder being plastic scraps;

[0056] The preparation steps of the composite flame retardant are as follows:

[0057] A1: Add ammonium polyphosphate to anhydrous ethanol at a solid-liquid ratio of 1g:2.5mL, stir and dissolve to obtain an ammonium polyphosphate solution, and add graphene oxide to deionized water at a solid-liquid ratio of 1g:60mL, stir and disperse to obtain a graphene oxide dispersion;

[0058] A2: The above ammonium polyphosphate solution and graphene oxide dispersion were fully stirred and mixed in a volume ratio of 1:2, and then heated at 40°C and ultrasonically treated for 20 hours, and then centrifuged, washed and dried to obtain a composite coating material;

[0059] A3: Add 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to dimethylformamide at a solid-liquid ratio of 1g:30mL, stir thoroughly to dissolve, then add the above composite coating material, ultrasonically treat for 20min, and fully disperse to obtain a composite dispersion, wherein the mass ratio of the composite coating material to 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 1:2;

[0060] A4: Add epichlorohydrin to the composite dispersion, heat and stir at 75-85°C for 3-4h, cool naturally to room temperature, filter, wash and dry to obtain a composite flame retardant, wherein the amount of epichlorohydrin added is 4-6% by mass of the composite dispersion;

[0061] The preparation steps of the modified composite antibacterial agent are as follows:

[0062] B1: Mix the composite antibacterial agent with deionized water and anhydrous ethanol at a solid-liquid ratio of 1g:1mL:20mL, stir for 20min, and ultrasonically disperse for 10min to obtain a composite antibacterial agent dispersion;

[0063] B2: Add γ-methacryloxypropyltrimethoxysilane to the above composite antibacterial agent dispersion, add sodium hydroxide solution to adjust the pH to 5, then heat and stir under reflux at 70°C for 3h, filter, wash and dry to obtain a surface-modified composite antibacterial agent, wherein the amount of silane coupling agent added is 6% of the mass percentage of the composite antibacterial agent dispersion;

[0064] B3: Add the surface modified composite antibacterial agent into white oil at a mass ratio of 1:46, stir and disperse thoroughly to obtain liquid A;

[0065] B4: Add acrylamide and acrylic acid to deionized water in a volume ratio of 1:3:90, stir and mix thoroughly, then add N,N'-methylenebisacrylamide at a mass percentage of 0.1% of acrylamide, continue stirring and mixing, and obtain liquid B;

[0066] B5: Evenly mix the above-mentioned liquid A and liquid B of equal mass, ultrasonically emulsify for 20 minutes, add ammonium persulfate, heat and stir under argon protection at 60°C for 4 hours, and then centrifuge, wash and dry to obtain a modified composite antibacterial agent, wherein the added amounts of ammonium persulfate and N,N'-methylenebisacrylamide are equal;

[0067] The preparation steps of the composite antibacterial agent are as follows:

[0068] C1: Add zinc nitrate hexahydrate into methanol at a solid-liquid ratio of 1g:25mL, stir thoroughly to dissolve, and obtain a zinc nitrate solution;

[0069] C2: Add 2-methylimidazole to methanol at a solid-liquid ratio of 1g:40mL, stir thoroughly to dissolve, and obtain a 2-methylimidazole solution;

[0070] C3: adding the above 2-methylimidazole solution to the above zinc nitrate solution, ultrasonically treating for 10 minutes, fully mixing, and then adding bismuth nitrate solution while stirring to obtain a composite solution, wherein the volume ratio of zinc nitrate solution to 2-methylimidazole solution is 1:1.2, the volume ratio of bismuth nitrate solution to zinc nitrate solution is 1:90, and the concentration of bismuth nitrate solution is 1 mol / L;

[0071] C4: The above composite solution was transferred to a high-pressure reactor, heated at 120°C for 20 hours, naturally cooled to room temperature, filtered, washed and dried, and then placed in a muffle furnace for heat treatment at 300°C for 2 hours to obtain a composite antibacterial agent.

[0072] Example 2

[0073] A rapid recycling method for waste plastics, such as Figure 1 As shown, the following steps are included:

[0074] S1: Pre-treatment of waste plastics

[0075] The waste polyethylene plastic is cleaned and disinfected, and then placed in a grinder for full crushing to obtain plastic scraps;

[0076] S2: Stirring and mixing

[0077] The plastic scraps were passed through a 120-mesh sieve, and then placed in a high-speed mixer together with the modified composite antibacterial agent and the composite flame retardant, and mixed and stirred at a rate of 900 r / min for 1.5 hours to obtain a mixed material;

[0078] S3: Recycled polyethylene fiber

[0079] The mixed material, polyethylene resin and glass fiber are added into a screw injection molding machine, heated and melted for spinning, and stretched under the action of hot air to obtain recycled polyethylene fiber;

[0080] S4: Preparation of recycled cloth bags

[0081] The recycled polyethylene fibers are drawn by a drafting airflow, vertically directed to a drum, and collected on a flat plate, thermally bonded to form recycled cloth, and then the recycled cloth is processed into recycled cloth bags;

[0082] The raw material components of the recycled polyethylene fiber include, by mass percentage, 4% of a modified composite antimicrobial agent, 4% of a composite flame retardant, 12.5% ​​of a polyethylene resin and 17.5% of glass fiber, with the remainder being plastic scraps;

[0083] The preparation steps of the composite flame retardant are as follows:

[0084] A1: Add ammonium polyphosphate to anhydrous ethanol at a solid-liquid ratio of 1g:2mL, stir and dissolve to obtain an ammonium polyphosphate solution, and at the same time add graphene oxide to deionized water at a solid-liquid ratio of 1g:65mL, stir and disperse to obtain a graphene oxide dispersion;

[0085] A2: The ammonium polyphosphate solution and the graphene oxide dispersion were fully stirred and mixed in a volume ratio of 1:2.1, and then heated at 40-50°C and ultrasonically treated for 22 hours, and then centrifuged, washed and dried to obtain a composite coating material;

[0086] A3: Add 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to dimethylformamide at a solid-liquid ratio of 1g:35mL, stir thoroughly to dissolve, then add the above composite coating material, ultrasonically treat for 25min, and fully disperse to obtain a composite dispersion, wherein the mass ratio of the composite coating material to 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 1:3;

[0087] A4: epichlorohydrin is added to the composite dispersion, heated and stirred at 80°C for 3.5 hours, cooled naturally to room temperature, filtered, washed and dried to obtain a composite flame retardant, wherein the amount of epichlorohydrin added is 5% by mass of the composite dispersion;

[0088] The preparation steps of the modified composite antibacterial agent are as follows:

[0089] B1: Mix the composite antibacterial agent with deionized water and anhydrous ethanol at a solid-liquid ratio of 1g:1mL:25mL, stir for 25min, and ultrasonically disperse for 15min to obtain a composite antibacterial agent dispersion;

[0090] B2: Add γ-methacryloxypropyltrimethoxysilane to the above composite antibacterial agent dispersion, then add sodium hydroxide solution to adjust the pH to 5.5, then heat and stir under reflux at 75°C for 3.5h, filter, wash and dry to obtain a surface-modified composite antibacterial agent, wherein the amount of silane coupling agent added is 7% by mass of the composite antibacterial agent dispersion;

[0091] B3: Add the surface modified composite antibacterial agent into white oil at a mass ratio of 1:48, stir and disperse thoroughly to obtain liquid A;

[0092] B4: Add acrylamide and acrylic acid to deionized water in a volume ratio of 1:4:93, stir and mix thoroughly, then add N,N'-methylenebisacrylamide accounting for 0.2% of the mass percentage of acrylamide, continue to stir and mix, and obtain liquid B;

[0093] B5: Evenly mix the above-mentioned liquid A and liquid B of equal mass, ultrasonically emulsify for 25 minutes, add ammonium persulfate, heat and stir under argon protection at 65°C for 4.5 hours, and then centrifuge, wash and dry to obtain a modified composite antibacterial agent, wherein the added amounts of ammonium persulfate and N,N'-methylenebisacrylamide are equal;

[0094] The preparation steps of the composite antibacterial agent are as follows:

[0095] C1: Add zinc nitrate hexahydrate into methanol at a solid-liquid ratio of 1g:30mL, stir thoroughly to dissolve, and obtain a zinc nitrate solution;

[0096] C2: Add 2-methylimidazole to methanol at a solid-liquid ratio of 1g:45mL, stir thoroughly to dissolve, and obtain a 2-methylimidazole solution;

[0097] C3: adding the above 2-methylimidazole solution to the above zinc nitrate solution, ultrasonically treating for 15 minutes, fully mixing, and then adding bismuth nitrate solution while stirring to obtain a composite solution, wherein the volume ratio of zinc nitrate solution to 2-methylimidazole solution is 1:1.5, the volume ratio of bismuth nitrate solution to zinc nitrate solution is 1:95, and the concentration of bismuth nitrate solution is 1 mol / L;

[0098] C4: The above composite solution was transferred to a high-pressure reactor, heated at 125°C for 22 hours, naturally cooled to room temperature, filtered, washed and dried, and then placed in a muffle furnace for heat treatment at 350°C for 2.5 hours to obtain a composite antibacterial agent.

[0099] Example 3

[0100] A rapid recycling method for waste plastics, such as Figure 1 As shown, the following steps are included:

[0101] S1: Pre-treatment of waste plastics

[0102] The waste polyethylene plastic is cleaned and disinfected, and then placed in a grinder for full crushing to obtain plastic scraps;

[0103] S2: Stirring and mixing

[0104] The plastic scraps are passed through a 200-mesh sieve, and then placed in a high-speed mixer together with the modified composite antibacterial agent and the composite flame retardant, and mixed and stirred at a rate of 1000 r / min for 2 hours to obtain a mixed material;

[0105] S3: Recycled polyethylene fiber

[0106] The mixed material, polyethylene resin and glass fiber are added into a screw injection molding machine, heated and melted for spinning, and stretched under the action of hot air to obtain recycled polyethylene fiber;

[0107] S4: Preparation of recycled cloth bags

[0108] The recycled polyethylene fibers are drawn by a drafting airflow, vertically directed to a drum, and collected on a flat plate, thermally bonded to form recycled cloth, and then the recycled cloth is processed into recycled cloth bags;

[0109] The raw material components of the recycled polyethylene fiber include, by mass percentage, 5% of a modified composite antimicrobial agent, 5% of a composite flame retardant, 15% of a polyethylene resin and 20% of glass fiber, with the remainder being plastic scraps;

[0110] The preparation steps of the composite flame retardant are as follows:

[0111] A1: Add ammonium polyphosphate to anhydrous ethanol at a solid-liquid ratio of 1g:3.5mL, stir and dissolve to obtain an ammonium polyphosphate solution, and add graphene oxide to deionized water at a solid-liquid ratio of 1g:70mL, stir and disperse to obtain a graphene oxide dispersion;

[0112] A2: The ammonium polyphosphate solution and the graphene oxide dispersion were fully stirred and mixed in a volume ratio of 1:2.2, and then heated at 50°C and ultrasonically treated for 24 hours, and then centrifuged, washed and dried to obtain a composite coating material;

[0113] A3: Add 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to dimethylformamide at a solid-liquid ratio of 1g:40mL, stir thoroughly to dissolve, then add the above composite coating material, ultrasonically treat for 30min, and fully disperse to obtain a composite dispersion, wherein the mass ratio of the composite coating material to 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 1:4;

[0114] A4: Add epichlorohydrin to the composite dispersion, heat and stir at 85°C for 4 hours, cool naturally to room temperature, filter, wash and dry to obtain a composite flame retardant, wherein the amount of epichlorohydrin added is 6% by mass of the composite dispersion;

[0115] The preparation steps of the modified composite antibacterial agent are as follows:

[0116] B1: Mix the composite antibacterial agent with deionized water and anhydrous ethanol at a solid-liquid ratio of 1g:1mL:30mL and stir for 30min, and ultrasonically disperse for 20min to obtain a composite antibacterial agent dispersion;

[0117] B2: Add γ-methacryloxypropyltrimethoxysilane to the above composite antibacterial agent dispersion, add sodium hydroxide solution to adjust the pH to 6, then heat and stir under reflux at 80°C for 4 hours, filter, wash and dry to obtain a surface-modified composite antibacterial agent, wherein the amount of silane coupling agent added is 8% by mass of the composite antibacterial agent dispersion;

[0118] B3: Add the surface modified composite antibacterial agent into white oil at a mass ratio of 1:50, stir and disperse thoroughly to obtain liquid A;

[0119] B4: Add acrylamide and acrylic acid to deionized water in a volume ratio of 1:5:96, stir and mix thoroughly, then add N,N'-methylenebisacrylamide accounting for 0.3% of the mass percentage of acrylamide, continue stirring and mixing, and obtain liquid B;

[0120] B5: Evenly mix the above-mentioned liquid A and liquid B of equal mass, ultrasonically emulsify for 30 minutes, add ammonium persulfate, heat and stir under reflux reaction at 70°C for 5 hours under the protection of argon, and then centrifuge, wash and dry to obtain a modified composite antibacterial agent, wherein the added amounts of ammonium persulfate and N,N'-methylenebisacrylamide are equal;

[0121] The preparation steps of the composite antibacterial agent are as follows:

[0122] C1: Add zinc nitrate hexahydrate into methanol at a solid-liquid ratio of 1g:35mL, stir thoroughly to dissolve, and obtain a zinc nitrate solution;

[0123] C2: Add 2-methylimidazole to methanol at a solid-liquid ratio of 1g:50mL, stir thoroughly to dissolve, and obtain a 2-methylimidazole solution;

[0124] C3: adding the 2-methylimidazole solution to the zinc nitrate solution, ultrasonically treating for 20 minutes, fully mixing, and then adding the bismuth nitrate solution while stirring to obtain a composite solution, wherein the volume ratio of the zinc nitrate solution to the 2-methylimidazole solution is 1:1.8, the volume ratio of the bismuth nitrate solution to the zinc nitrate solution is 1:110, and the concentration of the bismuth nitrate solution is 1 mol / L;

[0125] C4: The above composite solution was transferred to a high-pressure reactor, heated at 130°C for 24 hours, naturally cooled to room temperature, filtered, washed and dried, and then placed in a muffle furnace for heat treatment at 400°C for 3 hours to obtain a composite antibacterial agent.

[0126] Comparative Example 1

[0127] The difference from Example 1 is that the composite flame retardant in step S2 is removed.

[0128] Comparative Example 2

[0129] The difference from Example 1 is that the composite flame retardant in step S2 is replaced by an equal amount of composite coating material.

[0130] Comparative Example 3

[0131] The only difference from Example 1 is that the modified composite antibacterial agent in step S2 is removed.

[0132] Comparative Example 4

[0133] The difference from Example 1 is that the modified composite antibacterial agent in step S2 is replaced by an equal amount of composite antibacterial agent.

[0134] Comparative Example 5

[0135] The difference from Example 1 is that zinc nitrate hexahydrate and 2-methylimidazole in the preparation step of the composite antibacterial agent are removed to prepare bismuth oxide, and the composite antibacterial agent in step B1 is replaced by an equal amount of bismuth oxide.

[0136] Comparative Example 6

[0137] The difference from Example 1 is that the bismuth nitrate solution in the preparation step of the composite antibacterial agent is removed to prepare the zinc-based organic metal framework, and the composite antibacterial agent in step B1 is replaced by an equal amount of the zinc-based organic metal framework.

[0138] Performance Test:

[0139] Test 1: According to GB / T2406.2-2009, the limiting oxygen index (LOI) of the recycled fabrics prepared in Examples 1-3 and Comparative Examples 1-2 was tested using a Dynisco limiting oxygen index tester. The size of the recycled fabric sample was 10 cm×10 cm. The results are shown in Table 1.

[0140] Table 1: Comparison of the limiting oxygen index (LOI) of recycled fabrics of Examples 1-3 and Comparative Example 1

[0141] LOI value (%) Example 1 36.2 Example 2 36.1 Example 3 36.3 Comparative Example 1 17.8 Comparative Example 2 26.4

[0142] As can be seen from Table 1, the limiting oxygen index of the recycled cloth obtained by adding no composite flame retardant in Comparative Example 1 is about 17.8%, which is much smaller than that in Example 1, Example 2, and Example 3, while the limiting oxygen index of the recycled cloth obtained by adding the composite coating material without 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate grafting modification in Comparative Example 2 is about 26.4%, which is also smaller than that in Example 1, Example 2, and Example 3. It can be seen that by first preparing the ammonium polyphosphate solution and the graphene oxide dispersion separately, and mixing the ammonium polyphosphate solution with the graphene oxide dispersion, the residual oxygen index of the recycled cloth is about 17.8%, which is much smaller than that in Example 1, Example 2, and Example 3. The composite coating material is prepared by ultrasonic treatment of graphene dispersion, and the ammonium polyphosphate is loaded on graphene oxide with a high specific area to improve the stability and flame retardant properties of the ammonium polyphosphate. Finally, the composite coating material is mixed with 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to prepare a composite flame retardant. The surface of the composite coating material is grafted with 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to improve the compatibility between the composite flame retardant and waste polyethylene plastics, thereby improving the flame retardant properties of the recycled cloth bag.

[0143] Test 2: The antibacterial properties of the regenerated cloths prepared in Examples 1-3 and Comparative Examples 3-6 were tested by an oscillation method according to GB / T20944.3-2008. The results are shown in Table 2.

[0144] Test 3: The recycled cloths prepared in Examples 1-3 and Comparative Examples 5-6 were washed 20 times, and then tested for their antibacterial properties using an oscillation method according to GB / T20944.3-2008. The results are shown in Table 3.

[0145] Table 2: Comparison of antibacterial properties of recycled cloth of Examples 1-3 and Comparative Examples 3-4

[0146] Escherichia coli antibacterial rate (%) Antibacterial rate of Staphylococcus aureus (%) Example 1 96.3 94.9 Example 2 95.8 93.1 Example 3 95.9 93.3 Comparative Example 3 23.7 27.5 Comparative Example 4 82.2 79.7 Comparative Example 5 86.5 84.4 Comparative Example 6 84.3 82.8

[0147] Table 3: Comparison of antibacterial properties of recycled cloth of Examples 1-3 and Comparative Examples 5-6 after washing 20 times

[0148] Antibacterial rate of Escherichia coli after washing 20 times (%) Antibacterial rate of Staphylococcus aureus after washing 20 times (%) Example 1 93.5 91.5 Example 2 93.1 90.4 Example 3 93.3 90.2 Comparative Example 5 63.2 61.3 Comparative Example 6 56.8 53.7

[0149] It can be seen from Tables 2 and 3 that the resistance of the regenerated cloth prepared in Comparative Example 3 without adding the modified composite antibacterial agent to Escherichia coli and Staphylococcus aureus is 23.7% and 27.5%, respectively, while in Comparative Examples 5 and 6, after the composite antibacterial agent is replaced with a single bismuth oxide or a single zinc-based organic metal framework, the resistance of the regenerated cloth to Escherichia coli and Staphylococcus aureus is lower than that of Example 1, Example 2 and Example 3, and after washing 20 times, the resistance of the regenerated cloth prepared in Comparative Examples 5 and 6 to Escherichia coli and Staphylococcus aureus is reduced by 20-30%, while in Examples 1-3, it is only reduced by less than 5%. %, thus, it can be seen that by first dissolving zinc nitrate hexahydrate and 2-methylimidazole in methanol respectively to prepare zinc nitrate solution and 2-methylimidazole solution, and then fully mixing the silver nitrate solution and the 2-methylimidazole solution, and adding bismuth nitrate solution to heat and react to prepare a composite antibacterial agent, bismuth oxide with antibacterial activity is uniformly loaded on the porous zinc-based metal-organic framework. Since metallic zinc also has certain antibacterial activity, after bismuth oxide is loaded on the zinc-based metal-organic framework, not only can the antibacterial durability of bismuth oxide be improved, but the two can also synergistically fight bacteria, so that the prepared composite antibacterial agent has a better and longer-term antibacterial effect.

[0150] In addition, it can be seen from Table 2 that the resistance of the recycled cloth directly prepared using the composite antibacterial agent in Comparative Example 4 to Escherichia coli and Staphylococcus aureus is lower than that in Example 1, Example 2, and Example 3. It can be seen that the composite antibacterial agent is first uniformly dispersed in a mixed solution of deionized water and anhydrous ethanol, and then a silane coupling agent is added to react, the composite antibacterial agent is surface-modified, and then the surface-modified composite antibacterial agent is surface-grafted copolymerized with acrylamide and acrylic acid under the conditions of a cross-linking agent and ammonium persulfate initiator, so as to modify the composite antibacterial agent to improve the compatibility between the composite antibacterial agent and the waste polyethylene plastic, thereby achieving the effect of improving the antibacterial properties of the obtained recycled finished plastic bag.

[0151] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for rapid regeneration of waste plastics, characterized in that: The steps include: S1: Pre-treatment of waste plastics The waste polyethylene plastic is cleaned and disinfected, and then placed in a grinder for full crushing to obtain plastic scraps; S2: Stirring and mixing The plastic scraps are passed through a 100-200 mesh sieve, and then placed in a high-speed mixer together with the modified composite antibacterial agent and the composite flame retardant, and mixed and stirred at a rate of 800-1000 r / min for 1-2 hours to obtain a mixed material; S3: Recycled polyethylene fiber The mixed material, polyethylene resin and glass fiber are added into a screw injection molding machine, heated and melted for spinning, and stretched under the action of hot air to obtain recycled polyethylene fiber; S4: Preparation of recycled cloth bags The recycled polyethylene fibers are drawn by a drafting airflow, vertically directed to a drum, and collected on a flat plate, thermally bonded to form recycled cloth, and then the recycled cloth is processed into recycled cloth bags; Calculated by mass percentage, the raw material components of the recycled polyethylene fiber include: 3-5% modified composite antibacterial agent, 3-5% composite flame retardant, 10-15% polyethylene resin and 15-20% glass fiber, and the remainder is plastic scraps.

2. The method for rapid regeneration of waste plastics according to claim 1, characterized in that: The preparation steps of the composite flame retardant are as follows: A1: Add ammonium polyphosphate to anhydrous ethanol at a solid-liquid ratio of 1g:(2.5-3.5)mL, stir and dissolve to obtain an ammonium polyphosphate solution, and add graphene oxide to deionized water at a solid-liquid ratio of 1g:(60-70)mL, stir and disperse to obtain a graphene oxide dispersion; A:2: The above ammonium polyphosphate solution and graphene oxide dispersion are fully stirred and mixed, and then heated at 40-50°C and ultrasonically treated for 20-24h, and then centrifuged, washed and dried to obtain a composite coating material; A3: Add 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate to dimethylformamide at a solid-liquid ratio of 1g:(30-40)mL, stir thoroughly to dissolve, then add the above composite coating material, ultrasonically treat for 20-30min, fully disperse, and obtain a composite dispersion; A4: Add epichlorohydrin to the above composite dispersion, heat and stir at 75-85°C for 3-4 hours, cool naturally to room temperature, filter, wash and dry to obtain a composite flame retardant.

3. The method for rapid regeneration of waste plastics according to claim 1, characterized in that: The preparation steps of the modified composite antibacterial agent are as follows: B1: Mix the composite antibacterial agent with deionized water and anhydrous ethanol at a solid-liquid ratio of 1 g: 1 mL: (20-30) mL, stir for 20-30 min, and ultrasonically disperse for 10-20 min to obtain a composite antibacterial agent dispersion; B2: Add silane coupling agent to the above composite antibacterial agent dispersion, then add sodium hydroxide solution to adjust the pH to 5-6, then heat and stir under reflux at 70-80°C for 3-4h, filter, wash and dry to obtain a surface-modified composite antibacterial agent; B3: Add the surface modified composite antibacterial agent into white oil at a mass ratio of 1:(46-50), stir and disperse thoroughly to obtain liquid A; B4: Add acrylamide and acrylic acid to deionized water in a volume ratio of 1: (3-5): (90-96), stir and mix thoroughly, then add a crosslinking agent, continue stirring and mixing to obtain liquid B; B5: Evenly mix equal masses of the above-mentioned liquid A and liquid B, ultrasonically emulsify for 20-30 minutes, add ammonium persulfate, heat and stir under argon protection at 60-70°C for reflux reaction for 4-5 hours, and then centrifuge, wash and dry to obtain a modified composite antibacterial agent.

4. The method for rapid regeneration of waste plastics according to claim 1, characterized in that: The preparation steps of the composite antibacterial agent are as follows: C1: Add zinc nitrate hexahydrate into methanol at a solid-liquid ratio of 1 g: (25-35) mL, stir thoroughly to dissolve, and obtain a zinc nitrate solution; C2: Add 2-methylimidazole to methanol at a solid-liquid ratio of 1 g: (40-50) mL, stir thoroughly to dissolve, and obtain a 2-methylimidazole solution; C3: adding the 2-methylimidazole solution to the zinc nitrate solution, ultrasonically treating for 10-20 minutes, mixing thoroughly, and then adding the bismuth nitrate solution while stirring to obtain a composite solution; C4: The above composite solution is transferred to a high-pressure reactor, heated at 120-130°C for reaction for 20-24 hours, naturally cooled to room temperature, filtered, washed and dried, and then placed in a muffle furnace for heat treatment at 300-400°C for 2-3 hours to obtain a composite antibacterial agent.

5. The method for rapid regeneration of waste plastics according to claim 2, characterized in that: The volume ratio of the ammonium polyphosphate solution to the graphene oxide dispersion is 1:(2-2.2).

6. The method for rapid regeneration of waste plastics according to claim 2, characterized in that: The mass ratio of the composite coating material to 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is 1:(2-4), and the added amount of epichlorohydrin is 4-6% of the mass percentage of the composite dispersion.

7. The method for rapid regeneration of waste plastics according to claim 3, characterized in that: The silane coupling agent is gamma-methacryloxypropyltrimethoxysilane, and the added amount of the silane coupling agent is 6-8% of the mass percentage of the composite antibacterial agent dispersion.

8. The method for rapid regeneration of waste plastics according to claim 3, characterized in that: The cross-linking agent is N,N'-methylenebisacrylamide, and the added amount of the cross-linking agent is 0.1-0.3% of the mass percentage of acrylamide, and the added amounts of ammonium persulfate and the cross-linking agent are equal.

9. The method for rapid regeneration of waste plastics according to claim 4, characterized in that: The volume ratio of zinc nitrate solution to 2-methylimidazole solution is 1:(1.2-1.8).

10. The method for rapid regeneration of waste plastics according to claim 4, characterized in that: The volume ratio of the bismuth nitrate solution to the zinc nitrate solution is 1:(90-110), and the concentration of the bismuth nitrate solution is 1 mol / L.